다단계 Phytoreator을 이용한 영양물질 제거에 대한 연구 - 이상화; 최승일; 남연우; Janjit Iamchaturapatr; 이재성 (한국환경분석학회, 2009)
In this study, we investigated the performance of phytoremediation system treating wastewater containing high level of nutrients. Use of Acorus gramineus showed high removal efficiency for nitrogen (N) and chemical oxygen demand (COD) but low removal efficiency for phosphorus (P). The Overall N, P and COD removals efficiencies were 83.0-90.8.%, 12.8-40.6% and 72.6%, respectively. During the 9day operation of the system, The pH of effluent has significantly decreased comparing with raw water The mean pH of influent and effluent water was 6.0 and 7.0, respectively.